2019
DOI: 10.1111/xen.12481
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin photo‐cross‐linking method for improving elastin stability and reducing calcification in bioprosthetic heart valves

Abstract: Background:Glutaraldehyde cross-linked bioprosthetic heart valves might fail due to progressive degradation and calcification. Methods:In this study, we developed a new BHVs preparation strategy named as "HPA/TRA/FMN" that utilized 3,4-hydroxyphenylpropionic acid (HPA)/tyramine (TRA) conjugated pericardium and riboflavin 5'-monophosphate (FMN) initiated photo-cross-linking method. HPA/TRA-pericardium conjugation would provide extra phenol groups for FMN initiated photo-cross-linking. Results:The feeding ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…[29] However, the toxic aldehyde residues can affect the activity of phospholipids, enabling the binding of calcium ions. [30] To relieve the calcification degree of biological valves, many natural crosslinkers such as riboflavin, [31,32] tannic acid [33][34][35] and tea polyphenol [36] have been excavated, which reveal lower cytotoxicity and better biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…[29] However, the toxic aldehyde residues can affect the activity of phospholipids, enabling the binding of calcium ions. [30] To relieve the calcification degree of biological valves, many natural crosslinkers such as riboflavin, [31,32] tannic acid [33][34][35] and tea polyphenol [36] have been excavated, which reveal lower cytotoxicity and better biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19,20 ] Thus, excellent mechanical properties exert as a fundamental requirement during the development of valve scaffolds as scaffolds with poor mechanical properties would undergo rapid wear‐and‐tear and result in deterioration and calcification. In the past, various cross‐linking agents had been used to improve scaffold mechanical strength including carbodiimide, [ 21 ] riboflavin, [ 22 ] procyanidins, [ 23 ] curcumin [ 24 ] and so on. However, while GLUT will result in inevitable calcification, universally agreed alternative cross‐linkers outperforming GLUT remained lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Biomacromolecules modified with tyramine and its analogs could undergo cross-coupling reactions between the grated phenolic groups through riboflavin-mediated photo-crosslinking [ 124 , 125 ]. Lei et al [ 98 ] reported that coupling reactions ( Figure 3A ) between phenol groups on tyrosine and p-hydroxyphenylpropionic acid grafted BHVs were initiated under the catalysis of riboflavin and ultraviolet light to achieve the crosslinking of BHVs. This crosslinking strategy for BHVs allowed for greater utilization of reactive groups (amine and carboxyl groups) on BHVs compared with the conventional glutaraldehyde crosslinking method [ 98 ].…”
Section: Nonglutaraldehyde Crosslinking and Modification Strategies F...mentioning
confidence: 99%
“…Lei et al [ 98 ] reported that coupling reactions ( Figure 3A ) between phenol groups on tyrosine and p-hydroxyphenylpropionic acid grafted BHVs were initiated under the catalysis of riboflavin and ultraviolet light to achieve the crosslinking of BHVs. This crosslinking strategy for BHVs allowed for greater utilization of reactive groups (amine and carboxyl groups) on BHVs compared with the conventional glutaraldehyde crosslinking method [ 98 ]. Elastin on BHVs’ matrix was effectively stabilized to avoid the elastin degradation-induced calcification [ 98 ].…”
Section: Nonglutaraldehyde Crosslinking and Modification Strategies F...mentioning
confidence: 99%